PEMANFAATAN CERITA DAN GAMBAR UNTUK MENINGKATKAN KEPEDULIAN ANAK TERHADAP LINGKUNGAN DANAU SENTANI, PAPUA - Ohee, Henderite L.; Keiluhu, Henderina J.; Numberi, Vrinsye I.; Ngamelubun, Gerardinalia; Marani , Gilberth V.O.; Siahaan , Andro Y. (JURNAL PENGABDIAN PAPUA, 2023)
It is important to teach children about the need to maintain and protect Lake Sentani on a regular basis. Various activities have been carried out in some villages around Lake Sentani to increase children ‘s knowledge and concern for Lake Sentani. Environmental literacy on Lake Sentani was taught through stories and pictures to increase children's awareness of the environment in and around Lake Sentani. The program was carried out in Yokiwa Village in cooperation with Village Library: Sanggar Napas Danau Sentani, for ten months, starting in March and will end on December 2023. Socialization activities were carried out on May 6 and June 23, 2023, which were then followed by storytelling activities on June 24, 2023, and coloring activities on July 1, 2023. Stories about fish of Lake Sentani and Sentani folklore are told to children, then continued with them coloring the pictures. Evaluation of activities is carried out by asking children to retell these stories in their own words and discussing actions that can be taken to protect the environment of Lake Sentani. Children were actively listening to the stories which showed their ability to answer the questions given after and their good response to what they should do to their environment. Coloring and listening to story tales are very interesting activities for kids so they participated in them with great enthusiasm. Storytelling and coloring activities are some effective ways to remind children to protect their environment. Keywords: environmental literacy; Sentani Folklore; Fish of Lake Sentani; storytelling; coloring.